Stenotrophomonas maltophilia Infections in Adults: Primary Bacteremia and Pneumonia - Gokhan Gozel, Mustafa (Jundishapur J Microbiol, 2015)
BACKGROUND: Stenotrophomonas maltophilia is the third most frequent non-fermentative Gram-negative bacilli in nosocomial infections, and usually causes severe infections such as primary bacteremia and pneumonia. OBJECTIVES: The current study aimed to compare the demographic and clinical characteristics, microbiological findings and final outcomes of the patients with primary bacteremia and nosocomial pneumonia caused by S. maltophilia. PATIENTS AND METHODS: The current study retrospectively evaluated patients aged 18 years and above with primary bacteremia and nosocomial pneumonia caused by S. maltophilia from January 2006 to December 2013. Medical records of patients, including reports of clinical microbiology and hospital infection control committee, were evaluated. RESULTS: A total of 71 patients with S. maltophilia nosocomial infections, 35 (49.3%) primary bacteremia and 36 (50.7%) pneumonia, were diagnosed. There were no significant differences in gender, age, and co-morbid diseases, except chronic obstructive pulmonary disease; this infection was significantly higher in patients with pneumonia. A slightly higher 14-day mortality was found in patients with pneumonia, but the difference was not statistically significant. Inappropriate antibiotic use and presence of multiple organ dysfunction syndrome were found as independent risk factors for 14-day mortality in multivariate analysis. CONCLUSIONS: A slightly higher mortality in patients with pneumonia, caused by S. maltophilia, was strived to explain by advanced age, higher acute physiology and chronic health evaluation (APACHE II) and sepsis related organ failure assessment (SOFA) score, and also higher inappropriate antibiotic use.